Effects of leading-edge separation on the vortex-induced vibration of an elongated bluff body. Issue 209 (February 2021) - Duan, Guiyue; Laima, Shujin; Chen, Wenli; Li, Hui
Abstract: Wind-tunnel experiments were conducted to investigate the effects of leading-edge separation on the vortex-induced vibration (VIV) of an elastically-supported elongated bluff body. Solid wind barriers of various heights were fixed in the leading edge to adjust the flow separation. The vibration signals and the flow field information are acquired simultaneously by a laser-displacement system and particle image velocimetry (PIV) instrument respectively. The result shows that the VIV is excited by consecutive vortices shedding from the leading-edge shear layer. There is a critical height-to-thickness ratio ( h / t ) c r i t i c a l = 0.4, the VIVs are observed when h / t ≥ 0.4, while they are suppressed owing to the insignificant leading-edge separation when h / t < 0.4 . Three types of VIV are found, two of them are torsional VIV while another one is vertical VIV, which are named T1, T2, and V1 respectively. By placing a wake splitter plate at the trailing edge, V1 is suppressed entirely, T1 is weakened despite the slightly lower amplitude, while T2 transits to limit-cycle oscillations. The flow field information shows that the evolution and shedding pattern of leading-edge vortices vary from mode to mode. The status of the upper-layer leading-edge separated layer significantly affects the formation and the shedding of the trailing-edge vortices. The results reveal that leading-edge separation can play a dominant role in the vortex-induced vibrations of elongated bluff bodies. Highlights: Effects of the leading-edge separation on VIV has been investigated experimentally at a wide range of Re. Karman vortices are found when the leading-edge separation is not significant, which induce no vibrations. Three modes of VIV are found to be excited by the interaction between LEVs and TEVs. T2 mode VIV transits to the LCO mode when the upper- and lower-layers' interaction is prevented by a wake splitter plate. Patterns of vortex shedding are found to be different among T1, T2, V1 and LCO modes.